(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Lavender farms have lately grown in popularity in Turkey. Lavender farming is becoming more popular as a source of essential oils and rural tourism, which raises a slew of concerns about production and marketing. Turkey is known for its medicinal although it only production increased oil, honeysuckle oil, and lemongrass oil to the entire world, it is known for its fragrant plant and fundamental gas production. The present interest in lavender production in the nation has emphasized the need for a deeper understanding and analysis of the worldwide lavender oil markets. For worldwide lavender petroleum products and commerce, however, numbers and a standardized information are lacking. This study aims to bring aggregate data, material, and expertise in terms of understanding and evaluate the price and operators of lavender oil in worldwide markets. Lavandula intermedia (lavandin) produces practically all of Turkey’s lavender, as well as the majority of the world’s lavender. Although lavandin essential oil is five times more expensive than L. angustifolia (genuine lavender) oil, L. angustifolia oil has been the most respected and wanted after almond oil. Bulgaria, France, and China are the world’s biggest lavender oil exporters, although several other nations have lately boosted their output. The global supply of lavender oil has tended to rise as plantations in Bulgaria have grown, although quantity and quality are dependent on climatic conditions. The primary driver of price determination is lavender oil demand, which does not change much from year to year. Increased consumer awareness of healthier goods made with natural and organic components, on the other hand, is anticipated to drive up demand. The issue is whether Turkey has the potential to become a global participant in the lavender oil industry. Lavender production is appealing because of its Despite its cheap operating costs, better profit rate, and significance in rural development, lavender petroleum is economically unviable for people going separately due to small farm sizes and a convoluted value chain, requiring them to stay at the outset of the production process. However, since good lavender oil would still have an industry, Hungary should depend on the effectiveness and structure of the entire value chain to be competitive in the marketplace.